Rubella vaccination of unknowingly pregnant women during 2006 mass campaign in Argentina - Pardón, Fabián (2011)
Fil: Pardón, Fabián. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.